HIV/AIDS, food supplementation and livelihood programs in Uganda: A way worward - Yager, Jessica E.; Kadiyala, Suneetha; Weise, Sheri D. (Public Library of Science, 2011)
Background Over the last decade, health, nutrition and policy experts have become increasingly aware of the many ways in which food insecurity and HIV infection negatively impact and reinforce one another. In response, many organizations providing HIV care began supplying food aid to clients in need. Food supplementation, however, was quickly recognized as an unsustainable and incomplete intervention. Many HIV care organizations therefore developed integrated HIV and livelihood programs (IHLPs) to target the root causes of food insecurity. Methods and Findings We conducted a qualitative study using in-depth interviews with 21 key informants who worked at seven organizations providing HIV care, food aid, or IHLPs in Kampala, Uganda in 2007-2008 to better understand the impact of IHLPs on the well-being of people living with HIV and AIDS (PLWHAs) and the challenges in transitioning clients from food aid to IHLPs. There was strong consensus among those interviewed that IHLPs are an important intervention in addressing food insecurity and its adverse health consequences among PLWHAs. Key informants identified three main challenges in transitioning PLWHAs from food supplementation programs to IHLPs: (1) lack of resources (2) timing of the transition and (3) logistical considerations including geography and weather. Factors seen as contributing to the success of programs included: (1) close involvement of community leaders (2) close ties with local and national government (3) diversification of IHLP activities and (4) close integration with food supplementation programs, all linked through a central program of HIV care. Conclusion Health, policy and development experts should continue to strengthen IHLPs for participants in need. Further research is needed to determine when and how participants should be transitioned from food supplementation to IHLPs, and to determine how to better correlate measures of food insecurity with objective clinical outcomes so as to better evaluate program results.